PLEASURE-SEEKING PERSONALITY OF Mc.MURPHY IN ONE FLEW OVER THE CUCKOO'S NEST MOVIE (1975): A PSYCHOANALYTIC APPROACH - Cahyaningsih, Asri Nur (2011)
The study is to reveal how the personality reflected of major character in One Flew Over the Cuckoos Nest movie directed by Millos Forman in 1975. The objectives of the study are to analyze the structural elements of the movie in order to identity the unity of the movie and to analyze the pleasure seeking of the major character using psychoanalytic approach. The object of the study is a One Flew Over the Cuckoos Nest movie directed by Millos Forman. In this research the writer employs the descriptive analysis as a type of the research. The data sources divided into two, namely primary data source and secondary data source. The primary data sources are taken from the text of the movie such as dialogues, character action and whole narration which are relevant to the object of analysis. The secondary data source includes the references from some book and internet. The methods of collecting data are observation and library research. The technique of analyzing data is descriptive. The result of the analysis shows the following conclusion. First, based on the structural analysis, it is clear that in this movie, the director wants to deliver a moral message that everyone needs his freedom to do what he needs. Second, based on the psychological analysis, it is clear that in this movie the director illustrates a psychological phenomenon in which the boundary between sanity and insanity is not quite clear.